Engaging Chemistry Learning: Combining Uno Flashcards And Assemblr Edu for Nomenclature Of Compound Material - Annisa Mutma’inna; Mahartika, Ira; Alfiah; Pangoloan Soleman Ritonga; Nofri Yuhelman (Chemistry Education Department of Education and Teaching Faculty, 2024)
Students nowadays are used to take the advantage of technological advances in their daily lives, especially for education. Thus, students prefer to learn with by the collaboration of the latest electronic media. Therefore, electronic media is a must for the learning process. The purpose of this study is to determine the level of validity and practicality of Uno flashcard learning media on Assemblr Edu-based application on nomenclature of compound materials. The type of the research is DDR (Design and Development Research) development model with the stages of analysis, design, and development. This research was conducted in 2 schools, SMA Cendana Pekanbaru and SMA IT Al-Fityah Pekanbaru. The data was collected by interviews and questionnaires. Then the data analyzed quantitatively and qualitatively. The validity level obtained from this product is 93% (very valid), while the level of practicality obtained by teachers is 95% (very practical), and the response rate from students is 90% (very practical). Based on these results, it can be concluded that the uno flashcard learning media based on Assemblr Edu application on nomenclature of compound material is very feasible and practical to use in the process of learning nomenclature of compound. The implication of this research is that it can provide new and innovative learning experiences to teachers and students.